Willis covered stent treatment for blood blister-like aneurysm: A meta-analysis of efficacy and safety - Tan, Jiahe; Song, Rui; Luo, Siyue; Fu, Wenqiao; Su, Jun; He, Zhaohui (Frontiers in Neurology, 2023)
Background Blood blister-like aneurysm (BBA) is a rare and special type of intracranial aneurysm with extremely high rates of rupture, morbidity, mortality, and recurrence. Willis Covered Stent (WCS) is a new device that is specifically designed for the treatment of intracranial complex aneurysms. However, the efficacy and safety of WCS treatment for BBA remain controversial. Thus, a high level of evidence is required to prove the efficacy and safety of WCS treatment. Methods A systematic literature review was performed using a comprehensive literary search in Medline, Embase, and Web of Science databases to identify studies related to WCS treatment for BBA. A meta-analysis was then conducted to incorporate the efficacy and safety outcomes, including intraoperative situation, post-operative situation, and follow-up data. Results Eight non-comparative studies containing 104 patients with 106 BBAs met the inclusion criteria. In the intraoperative situation, the technical success rate was 99.5% [95% confidence interval (CI), 0.958, 1.000], the complete occlusion rate was 98.2% (95% CI, 0.925, 1.000), and the side branch occlusion rate was 4.1% (95% CI, 0.001, 0.114). Vasospasm and dissection occurred in 9.2% (95% CI, 0.000, 0.261) and 0.1% (95% CI, 0.000, 0.032) of the patients, respectively. In the post-operative situation, the rebleed and mortality rates were 2.2% (95% CI, 0.000, 0.074) and 1.5% (95% CI, 0.000, 0.062), respectively. In the follow-up data, recurrence and parent artery stenosis occurred in 0.3% (95% CI, 0.000, 0.042) and 9.1% (95% CI, 0.032, 0.168) of the patients, respectively. Ultimately, 95.7% (95% CI, 0.889, 0.997) of the patients had a good outcome. Conclusions Willis Covered Stent could be effectively and safely applied for BBA treatment. The results provide a reference for clinical trials in the future. Well-designed prospective cohort studies must be conducted for verification.